Formation of Cr23C6 during the Sensitization of AISI 304 Stainless Steel and its Effect to Pitting Corrosion - A.R.M, Warikh; Mohd Rosli, ZULKIFLI; Gakim, Miron; M.A, ASYADI AZAM (2012)
The metallic carbide precipitation was observed after the sensitization of AISI 304 stainless steel specimens in neutral flame by using oxy-fuel and slowly cooled in the air. Correlation between corrosion and X-Ray Diffraction (XRD) shows that the enrichment of Cr23C6 in the microstructure of AISI 304 worsens the pitting corrosion resistance properties as the sensitization time increases from 5 to 60 s. However, the precipitation dissolved and corrosion resistance properties improved after the specimens treated in solution quenching treatment at 1130 oC, soaked from 24 – 120 min, then rapidly cooled in water.